A Comparative Investigation on Mechanical Properties of Various Fibers Reinforced Concrete - Ahmed Al-Ghaban; Hussein Jaber; Aya Shaher (Engineering and Technology Journal, 2019)
The present work presents an investigation the effect of adding various fiber materials such as (glass, nylon, and carbon) into the concrete mix for inspecting and compare the mechanical properties of different fibers reinforced concrete. Two different fiber length states of (short=3cm and long=10cm) are used in this work. The concrete of ordinary Portland cement of (1:1.5:3), (cement: sand: gravel), were mixed with each of the fiber materials at four different weight percentages (0, 0.4, 0.8, and 1.2) wt% per cement content. Compressive strength and flexural strength were experimentally investigated of different fibers reinforced concrete specimens after curing for 28 days. The results showed that the incorporation of various fibers with the concrete mix generally improved the strength of concrete by improving the toughness. The flexural strength of concrete with addition of various fibers was strongly enhanced than compression. Addition 0.8% of nylon fiber to concrete resulted in the maximum increase of its compressive strength, reaching the rate of increasing to 11.08% for short fiber and 20.75% for long fiber. Addition 1.2% of nylon fiber to concrete mix resulted in the maximum increase of the flexural strength, reaching rate of increasing to 120.02% for short fiber and 211.49% for long fiber. Increasing the length of fibers increases the strength of the concrete but a little extent. Among these fibers, nylon containing concrete composite exhibits promising mechanical strength that could be easily used as low-cost partitioning wall, false ceiling, and other household purposes.